Manajemen Pemerintahan Desa Sukaluyu Dalam Produktivitas Bumdes Jaya Perkasa - Nandira Maharani; Evi Priyanti (Universitas Muhammadiyah Sumatera Utara, 2023)
Village Owned Enterprises (BUMDes) are financial institutions developed by the government as a means of improving community welfare through the Community Empowerment and Village Development Agency. Based on the village's special potential, the village government and the community decided to build BUMDes. BUMDes must encourage community involvement in developing and prospering their village. For the village government, BUMDes can be a place to build and utilize the resources and potential of the village. The purpose of this study was to find out how far the management of village government has increased the productivity of BUMDes in Sukaluyu Village in planning, organizing, implementing and supervising. This research adopts the Qualitative Method. To observe and analyze village government management phenomena, qualitative methods are considered more relevant. The results of this study indicate that the management function can indeed be one of the benchmarks for an institution to be said to be productive or not, how BUMDes carry out their duties and functions from planning to oversight. It is hoped that it can run and improve the wheels of the village and community economy.Keywords: Mangement, Village Government, Village-Owned Enterprises.